2022
DOI: 10.1039/d1em00375e
|View full text |Cite
|
Sign up to set email alerts
|

Review of ecotoxicological studies of widely used polystyrene nanoparticles

Abstract: With polystyrene nanoparticles being widely used in various applications, there is a great need for deeper knowledge on the safety, fate and biological effects of these particles on both individual living organisms and the whole ecosystems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 86 publications
(112 reference statements)
1
15
0
Order By: Relevance
“…Compared to organism characterization and test parameters, much lower scores were found for physico-chemical properties of nanoPS. This result was in line with a previous review [ 2 ]. The data on impurities and additives, which are considered mandatory, are a bottleneck (only 36 % of studies reported impurities or additives, respectively).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Compared to organism characterization and test parameters, much lower scores were found for physico-chemical properties of nanoPS. This result was in line with a previous review [ 2 ]. The data on impurities and additives, which are considered mandatory, are a bottleneck (only 36 % of studies reported impurities or additives, respectively).…”
Section: Resultssupporting
confidence: 94%
“…Global plastic pollution and the detection of micro- and nanoplastic particles in almost all environmental compartments and geographic regions has fuelled research into the possible effects of these particles on environmental organisms. One specific research question is whether nanoplastic particles exert specific and/or enhanced effects in organisms in comparison to microplastics [ 1 , 2 , 3 , 4 ]. However, studies have reported different conclusions regarding this question.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a one of the most used plastics, PS NPs was selected as the representative model. , The morphologies and structures of pristine and aged NPs were observed with SEM. The pristine PS NPs were spherical in shape with smooth surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Humans may be exposed to NPs via inhalation, ingestion, or skin contact, thus posing a great threat to human health. , It was reported that NPs have various adverse effects, including mortality, developmental toxicity, endocrine toxicity, immunotoxicity, and genotoxicity. , Clearly, the aging process will dramatically affect the physicochemical properties of NPs and in turn affect their cytotoxicity . However, it is largely unknown how aging processes alter the biological/toxicological characteristics of NPs.…”
Section: Introductionmentioning
confidence: 99%